Gratitude and Negative Affects During the Covid-19 Pandemic: The Role of Comparative Thinking as Moderating Variables - Daud, Muh; Nugraha, Dwi Yan; Siswanti, Dian Novita; Zhalifunnas, Muhammad Shafwan (Journal of Educational, Health and Community Psychology, 2024)
College students have been shown to be more susceptible to mental health problems and psychological distress than the general population their age. The purpose of this study is to examine the moderating effect of comparative thinking on the relationship between gratitude and negative affect during the COVID-19 outbreak. A total of 370 students were recruited through an online questionnaire to obtain responses from a representative sample. Respondents filled out a questionnaire in the form of the gratitude questionnaire – six item form (GQ-6) and 20 items positive affect negative affect schedule (PANAS), as well as a question used to measure comparative thinking. The main result obtained in this study is that there is a significant moderating effect of comparative thinking in predicting gratitude towards negative affect. This finding, of course, can be used as a reference as the determination of training programs at the applied level and theoretical development of the gratitude model.